2017
DOI: 10.1161/circep.116.004400
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Concealed Nature of Long-QT Type 3 Syndrome

Abstract: Background Gain-of-function mutations in the voltage-gated sodium channel (Nav1.5) are associated with the long QT-3 (LQT3) syndrome. Nav1.5 is densely expressed at the intercalated disk, and narrow intercellular separation can modulate cell-to-cell coupling via extracellular electric fields and depletion of local sodium ion nanodomains. Models predict that significantly decreasing intercellular cleft widths slows conduction due to reduced sodium current driving force, termed “self-attenuation.” We tested the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
53
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 45 publications
17
53
0
Order By: Relevance
“…They observed small APs with a reduced amplitude that propagates and impacts conduction failure. In patients with long QT syndrome type 3, the distribution changes in Na + channels with the gain-of-function mutation have significantly affected the propagation in APs with early afterdepolarizations [44][45][46] . Also Jaeger et al 47 have demonstrated a mechanism of conduction failure due to changes in Na + channel distribution.…”
Section: Discussionmentioning
confidence: 99%
“…They observed small APs with a reduced amplitude that propagates and impacts conduction failure. In patients with long QT syndrome type 3, the distribution changes in Na + channels with the gain-of-function mutation have significantly affected the propagation in APs with early afterdepolarizations [44][45][46] . Also Jaeger et al 47 have demonstrated a mechanism of conduction failure due to changes in Na + channel distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that perinexal separation in guinea pig ventricular myocardium is approximately 12 nm ( Veeraraghavan et al, 2015 ). We later found with different observers that perinexal separation can vary between 10 and 25 nm depending on the ex vivo perfusate used to sustain the heart through studies ( George et al, 2015 , 2016 , 2017 ; Entz et al, 2016 ; Greer-Short et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sugrue et al 27 looked at cases of genetically confirmed cases of long-QT syndrome types 1 and 2 and found that left slope of the surface T wave in lead V6 and the T-wave center of gravity x axis (last 25% of the wave) in lead 1 were predictors of future long-QT syndrome-associated cardiac events, especially in long-QT syndrome type 2. Greer-Short et al 28 were interested in revealing the concealed nature of long-QT syndrome type 3 syndrome and looked at gain of function mutations in the voltage-gated Na channel (Nav1.5), which is associated with the long-QT syndrome type 3 syndrome. The authors showed that by increasing intercellular cleft width at cell-cell connections, this resulted in action potential duration prolongation and produced early after depolarizations, possibly triggering arrhythmogenesis.…”
Section: Long-qt Syndromementioning
confidence: 99%